Modelling nitrogen and carbon interactions in composting of animal manure in naturally aerated piles. (December 2015) - Oudart, D.; Robin, P.; Paillat, J.M.; Paul, E.
Graphical abstract: Highlights: Biological and physical modelling of composting of manure in passive aerated piles. Additional data NH3 emissions from manure in conditions similar to farm composting. Gas emissions are predicted for representative contrasted composting situations. Higher microbial growth decreases ammonia emission. Nitrogen availability can limit microbial growth even in the case of animal manure. Abstract: Composting animal manure with natural aeration is a low-cost and low-energy process that can improve nitrogen recycling in millions of farms world-wide. Modelling can decrease the cost of choosing the best options for solid manure management in order to decrease the risk of loss of fertilizer value and ammonia emission. Semi-empirical models are suitable, considering the scarce data available in farm situations. Eleven static piles of pig or poultry manure were monitored to identify the main processes governing nitrogen transformations and losses. A new model was implemented to represent these processes in a pile considered as homogeneous. The model is based on four modules: biodegradation, nitrogen transformations and volatilization, thermal exchanges, and free air space evolution. When necessary, the parameters were calibrated with the data set. The results showed that microbial growth could reduce ammonia volatilization. Greatest nitrogen conservation is achieved when microbial growth was limited by nitrogen availability.